Efficient key management scheme for health blockchain. Issue 2 (1st June 2018) - Zhao, Huawei; Bai, Peidong; Peng, Yun; Xu, Ruzhi
Abstract : Healthcare is a big application scenario of blockchain, and blockchains used in healthcare are called health blockchain. In general, blockchain blocks are open and the transactions in them are public. If some privacy data are involved in these transactions, they will be leaked. Owing to healthcare system involving a great deal of privacy data, certain security mechanisms must be built to protect these privacy data in health blockchain. Furthermore, because the core of security mechanisms is the key management schemes, the appropriate key management schemes should be designed before blockchains can be used in healthcare system. Here, according to the features of health blockchain, the authors use a body sensor network to design a lightweight backup and efficient recovery scheme for keys of health blockchain. The authors' analyses show that the scheme has high security and performance, and it can be used to protect privacy messages on health blockchain effectively and to promote the application of health blockchain.